Enzymatic esterification of acylglycerols rich in omega-3 from flaxseed oil by an immobilized solvent-tolerant lipase from Actinomadura sediminis UTMC 2870 isolated from oil-contaminated soil. (15th April 2018) - Imanparast, Somaye; Hamedi, Javad; Faramarzi, Mohammad Ali
Highlights: A solvent-tolerant lipase with high efficiency to ω-3 was isolated from A. sediminis . The enzyme showed marked stability under alkaline and acidic condition. The lipase was immobilized by physical adsorption onto Celite. Acylglycerols rich in ω-3 fatty acids were produced by the immobilized lipase. Abstract: Polyunsaturated fatty acids (PUFAs) are essential to human health and can be produced by enzymatic esterification. Actinomadura sediminis UTMC 2870 isolated from oil-contaminated soil contained a lipase that was stable at varying pH and in various solvents, salts, and chemicals. This lipase exhibited high efficiency for omega-3 (n-3), and its production was optimized using a response surface method. Acylglycerols (AGs) rich in n-3 were produced by extraction of the free fatty acids (FFAs) from flaxseed oil, concentration of PUFAs, and enzymatic esterification by the Celite-immobilized lipase. The resulting product contained 50% (w/w) PUFAs, including 42% (w/w) α-linolenic and 9.7% (w/w) linoleic acid. The n-6/n-3 ratio in the product was 0.24, which differed markedly from the high values for this ratio in seed oils. Therefore, the A. sediminis lipase appears to be a good candidate enzyme for ester synthesis and especially for production of n-3–rich AGs for food industries.